Generalized multidimensional scaling: a framework for isometry-invariant partial surface matching - Bronstein, Alexander M; Bronstein, Michael M; Kimmel, Ron (Proceedings of the National Academy of Sciences - PNAS, 2006)
An efficient algorithm for isometry-invariant matching of surfaces is presented. The key idea is computing the minimum-distortion mapping between two surfaces. For this purpose, we introduce the generalized multidimensional scaling, a computationally efficient continuous optimization algorithm for finding the least distortion embedding of one surface into another. The generalized multidimensional scaling algorithm allows for both full and partial surface matching. As an example, it is applied to the problem of expression-invariant three-dimensional face recognition.